Identifying the Dimensions and Consequences of Digital Customer Experience: A Phenomenological Study - Fatemeh Eslahi; Seyed Mohammad Reza Mirahmadi; Mojtaba Aghajani (‫مدیریت بازرگانی)
ObjectiveAchieving success, particularly in the realm of online and digital commerce, frequently hinges on customer experience, a multifaceted process influenced by numerous factors. Along with the emergence of new technologies, communication methods between organizations and customers have changed. The digitalization process allows customers to access a great deal of information around the world without any time or place boundaries and make multiple transactions and purchases at once. Today, customers are not only accessing and searching for information on the Internet but also engaging in interactions, uploading, and sharing content themselves. In addition, by creating the online virtual world, social media has transformed communication from traditional methods into a large and online social phenomenon. Utilizing interactive capabilities enables direct contact with consumers, resulting in lower costs, increased productivity, enhanced satisfaction with internet purchasing, higher repurchase intentions, and ultimately, a more pleasant consumer experience. Digital customer experience has become an important topic in market research, as businesses have realized that their success depends largely on providing positive purchasing experiences for their customers. Creating memorable experiences is significant for retaining old customers and attracting new ones. This study investigates the desired digital experience of customers when shopping online in a highly competitive environment. It also seeks to determine the factors contributing to the digital experience of customers in cyberspace.   MethodologyThe research employs a qualitative and descriptive phenomenological approach. The statistical population consists of individuals who engage in internet purchasing on websites at least twice a month, with a monthly purchasing amount exceeding 500 thousand Tomans. Accordingly, those who were fully familiar with Internet purchasing were selected as the study sample. Furthermore, a purposive sampling technique was used to select the samples and concerning the qualitative nature of the research, the sample size was determined to be 18 people until the data saturated. The interview data underwent analysis using Van Manen's method, which involved three stages of coding: open, axial, and selective coding. Throughout this process, the data were continuously reviewed and refined to ensure thorough analysis. FindingsA total of 705 codes were extracted after the data were analyzed. The codes were classified into three major components, including digital customer experience, satisfaction with internet purchasing, and repurchase intention. In total, digital customer experience encompassed 19 sub-categories, five main categories, and one sub-category. Customer satisfaction with Internet purchasing consisted of two categories and the repurchase intention consisted of two categories. ConclusionThe research findings highlight the influence of the aforementioned factors in fostering a favorable digital experience for customers and online shopping. It is worth noting that given the highly competitive conditions of businesses, managers and business owners should give special credit to these factors to achieve customer satisfaction.